The criminal jury at trial. The doctrinal opinions of French authors (1750-1830) - Soleil, Sylvain (2021)
The English model of the criminal jury was admired in the Europe of the Enlightenment, especially in France. Enthusiastically adopted by the revolutionaries (1790-1791), it became the object of very strong criticism because of the flawed practice of the system in the years 1792-1800. The Thermidoriens, then the members of the Directoire sought to rectify the operating of the double jury of accusation and judgment. In vain. A first doctrinal controversy erupted in the years 1798-1808, when Napoleon Bonaparte questioned whether the jury should be maintained or not. A second doctrinal controversy arose after the restoration of King Louis XVIII, in the years 1818-1828, when it was a question of rehabilitating the English jury as a symbol of balanced criminal justice, but also of going to England to observe how justice worked.